Does Corporate Social Responsibility Shape the Relationship between Corporate Governance and Financial Performance? - Jaja Suteja; Ardi Gunardi; Rani Janisa Auristi (Universitas Pasundan, 2017)
The correlation between theoretical and empirical of corporate governance (CG) and corporate financial performance (CFP) is not there without controversy. This paper aims to determine the moderating effects of corporate social responsibility (CSR), on the relationship between corporate governance and corporate financial performance. The sample of this research are banking companies that are listed on Indonesia Stock Exchange between the period of 2010-2014, taken by using purposive sampling method. Moderated Regression Analysis (MRA) analysis was used in this study. The results of this study indicate that corporate governance affects the company's financial performance positively. Aspects of corporate governance such as audit committees and number of board meetings have a positive relationship with financial performance, but there is no relationship from the aspect of independent board of commissioners. Furthermore, CSR can only strengthen the positive relationship between the number of board of commissioners’ meetings and the financial performance of the company. The frequency intensity of board of commissioners’ meetings can increasingly address corporate governance reforms by improving and realizing social responsibility as part of sustainability innovation by optimizing media and CSR reporting methods.